Risk Identification Of Roll Forming Machine Area With The (HIRARC) Approach at PT. Bumi Lestrai Karya Perkasa : Identifikasi Risiko Area Roll Forming Dengan Pendekatan (HIRARC) Di PT. Bumi Lestari Karya Perkasa - Febrianta Dwi Harianto; Hana Catur Wahyuni (Universitas Muhammadiyah Sidoarjo, 2023)
PT. Bumi Lestari Karya Perkasa experiences 25 workplace accidents in a year. The purpose of this study is to estimate the amount of potential work accident risks in the field of roll forming machines and to control risks with appropriate Personal Protective Equipment (PPE) to reduce occupational risks. The Hazard Identification Risk Assessment and Risk Control (HIRARC) method was used in this study. This research is a qualitative research. Field observations, literature study of company documents, and in-depth interviews with the SMK3 division at PT. Bumi Lestari Karya Perkasa is used to collect data. The risk score is calculated first in the analysis. This research resulted in identification of companies in an effort to improve the safety of all work in the roll forming machine area to avoid unsafe actions and unsafe conditions, as well as the use of Personal Protective Equipment (PPE) by adjusting the type of work being carried out and the lack of awareness about the importance of tools. Personal Protection (PPE). Highlights : Quantifying Risk: Using HIRARC method to assess and quantify potential work accident risks provides a structured approach to understanding and addressing safety concerns. Qualitative Research Approach: Employing field observations, literature study, and in-depth interviews allows for a comprehensive understanding of the factors contributing to workplace accidents. Emphasis on Prevention: Identifying unsafe actions and conditions underscores the importance of proactive measures, such as proper PPE usage and raising awareness among employees, to mitigate occupational risks. Keywords - Work Risk; Work Accident; Roll Forming